THE "INDIFFERENCE-ke CONSTRUCTION" IN MODERN CONVERSATIONAL PERSIAN - Sadat-Tehrani, Nima (Linguistica Atlantica, 2003)
This paper deals with a construction in Persian called here the Indifference-ke Construction (or IKC). This construction has the structure A ke B, where A is a clause (minimally a verb), ke is a particle, and B is a verb, a reduplication of the verb in A. The IKC has a certain intonation pattern and includes both the propositional attitude (that of indifference) and the propositional content at the same time. Analysis of the interaction between the IKC and compound verbs, scrambled sentences and various T/A/Ms (Tense/Aspect/Moods) concludes: The reduplicated element is always a yO. This article treats the phonological, syntactic and semantic/conceptual components of the IKC based on the theoretical framework of Jackendoff’s Parallel Architecture. These components are related through interfaces and none of them is considered to be the basic or underlying one.